Implications of judicial activism as constitutional overreach on the authority of the constitutional court - Budi Indra Cahaya; Alina Yuni Utami; Syedna Ahmad Albanna; Bagas Fadhilah Ananta Jaya; Octa Tesalonika (Privietlab, 2026)
This study discusses the authority of Indonesia’s Constitutional Court, or Mahkamah Konstitusi (MK), in relation to the exercise of judicial activism beyond its explicit constitutional mandate. We also discuss the constitution and constitutional obligations of the MK and finally we deal with judicial activism principle, whether it usurps from the power of parliament or not? This article, therefore, operates as conceptual research by undertaking literature review and analysis of related legal concepts. The study elucidates that the application of this principle has important consequences for the competences and position of the MK. Although it does increase the scope of potential protection for constitutional rights and the course of public policy, exercising judicial activism also calls into question to what extent judges can go beyond their roles and abuse their power. Accordingly, a long-term effect of the principle is that the MK should be held to account for decisions taken in light of this principle and strengthen mechanisms by which public accountability can take place. Fall-back mechanisms and constitutional reform to clarify the dispositions and bounds of the MK's ability to engage in judicial activism also must be pondered if integrityfulness, legitimacy and a balance between progressive law creation and observation of the constitution are desired to be preserved. Specific advice by way of constitutional amendments is also offered to limit the scope of the MK’s legal activism and augment the controlling function as a counterweight to misuse of powers. The proposed regulation is intended to enhance openness, accountability and public trust in the MK as an independent and committed law enforcement agency.